2015
DOI: 10.1016/j.eurpsy.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Measures of circadian preference in childhood and adolescence: A review

Abstract: The present state of the art would suggest the use of the MEQ-CA to assess circadian preference in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 73 publications
2
32
1
1
Order By: Relevance
“…38). The scale has undergone some validation studies in adults and adolescents639. For example, the scores obtained on the scale are stable over a period of some months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…38). The scale has undergone some validation studies in adults and adolescents639. For example, the scores obtained on the scale are stable over a period of some months.…”
Section: Methodsmentioning
confidence: 99%
“…8). Construct validity was obtained by actigraphy9, and the CSM scores correlated with about 0.5 with objectively measured bed and rise times639.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported good internal consistency, with Cronbach's alphas from 0.70 to 0.82 in American, Australian, Croatian, Dutch, Hong Kong-Chinese, Israeli, Italian, Spanish, Taiwanese and Turkish adolescent samples, good test-retest reliability (r = 0.80 to 0.83) and external validity using various behavioural outcomes in adolescents (Tonetti, Adan, Di Milia, Randler, & Natale, 2015). However, few studies have analysed the dimensionality of M-E measures among adolescents.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, the present meta-analytic review differs from that of Preckel et al (2011) for four main features. Firstly, we adopted an approach which considers circadian preference as an unidimensional construct, from which it derives the Morningness-Eveningness Questionnaire (MEQ) (Horne & Ö stberg, 1976), the most frequently used questionnaire worldwide to measure circadian preference (Di Milia et al, 2013); furthermore a recent review (Tonetti et al, 2015a) has suggested the use of the adaptation for children and adolescents based on the MEQ (MEQ-CA) to assess circadian preference in these populations. This unidimensional conceptualization is used worldwide by a large number of researchers, and there is evidence that circadian preference is unidimensional when analyzing the underlying biological rhythms, such as peak melatonin secretion, cortisol awakening response and sleep behavior.…”
Section: Introductionmentioning
confidence: 99%